GAMBARAN TINGKAT PENGETAHUAN MAHASISWI SEMESTER 2 TENTANG SADARI (PEMERIKSAAN PAYUDARA SENDIRI) DI PRODI DIII KEPERAWATAN STIKES PKU MUHAMMADIYAH SURAKARTA - Susanti, Ninik; Mintarsih, Sri (PROFESI || JURNAL KESEHATAN PROFESIONAL ISLAMI, 2013)
Background. Breast cancer is a disease where there is excessive growth or uncontrolled growth of cells (breast tissue), it can happen to women and men. Early detection of breast cancer is important because it is able to prevent conditions conducive to more severe breast cancer. Every young woman must to know about that. Breast self-examination (realized) in young women is breast self-examination is done manually. Reports from Western Breast Services Alliance, fibroadenoma generally occurs in women between the ages of 15 and 25 years. Another fact shows that about 85 % of women find lumps in their breasts through touch. Purpose. To determine the level of knowledge and overview of student behavior in the second semester of Nursing in STIKES PKU Muhammadiyah Surakarta. Research Methods. This study used a descriptive survey method with cross sectional approach. The population in this study is a Â student in second semester. Sampling with quota sampling technique, the sample size of 30 respondents. The instrument used was a questionnaire enclosed, direct measurement of distributing questionnaires to the respondents. The data is processed by SPSS version 16 with univariate data analysis. Results. The majority of respondents aged 18 years as many as 12 people (40.0 %). Most respondents did not ever realize that as many as 27 respondents (90 %), while the level of student knowledge about realizing that 21 respondents (70.0 %) were categorized either, 9 respondents (30 %) were categorized sufficient and no respondents who have less knowledge nor bad. Conclusion. The level of student knowledge realized in the second half of the DIII Nursing major in STIKES PKU Muhammadiyah Surakarta is good but they do not have the awareness to realize. Keywords : knowledge, knowing